Peanut, Butter, & Crackers. 02 : fetch! - Braddock, Paige (Peanut, Butter, & Crackers, 2021)
When he gets separated from Butter and Crackers, Peanut becomes the new target of the Pint-Sized Pack-the bullies of the Little Dogs group-and must find a way out of this predicament.